2020
DOI: 10.1002/ird.2523
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Economical Allocation of Irrigation Water under a Changing Environment: a Stochastic Multi‐Objective Nonlinear Programming Model*

Abstract: Water scarcity causes conflicts between natural resources and socio‐economic development which reinforces the need for optimal allocation of irrigation water resources. Irrigation water resource allocation is a complex problem due to various uncertainties in natural conditions. In this study, a stochastic multi‐objective nonlinear programming model is developed for irrigation water allocation under uncertainty. The model is capable of balancing the conflicting objectives of maximizing both net economic benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Water use efficiency is measured by the economic benefits generated per unit of water resources. After reviewing relevant literature [29,30] and considering the economic and social development of the planning year, the net efficiency coefficients for industrial and agricultural water supply were determined to be 175.4 yuan/m 3 and 11.2 yuan/m 3 , respectively. It is difficult to quantify the net benefits of domestic and ecological water supply.…”
Section: Model Parameter Settingmentioning
confidence: 99%
“…Water use efficiency is measured by the economic benefits generated per unit of water resources. After reviewing relevant literature [29,30] and considering the economic and social development of the planning year, the net efficiency coefficients for industrial and agricultural water supply were determined to be 175.4 yuan/m 3 and 11.2 yuan/m 3 , respectively. It is difficult to quantify the net benefits of domestic and ecological water supply.…”
Section: Model Parameter Settingmentioning
confidence: 99%
“…Climate conditions are a significant factor affecting water availability and demand (Loch & Adamson, 2015; Yan et al, 2021). The water available as a result of increased irrigation efficiency includes both regular and saved water.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Thus, the findings of this study showed that nearly 38% of the arable land in the project location had irrigation coverage. The quality of irrigation services, agricultural water productivity and efficiency at the farm level throughout the world are not satisfactory (Huang et al, 2007;Koo-Oshima, 2023;Yan et al, 2021). Lovelli et al (2017) identified the following three key factors necessary to improve agricultural water productivity: (a) sustainability in use of environmental resources, (b) food security and (c) growers' income increment due to judicial use of water.…”
Section: Irrigation Service Statusmentioning
confidence: 99%